(untitled) (Research, Society and Development, 2022)
Entropion is an ophthalmic condition that occurs when the palpebral margin is partially or totally inverted, allowing the eyelash on the outer portion of the eyelid to come into contact with the cornea and/or the conjunctiva, being accentuated by the exuberant nasal folds in brachycephalic dogs, which frequently present ocular alterations related to racial predisposition due to their anatomical conformation. The clinical signs found include epiphora, mucopurulent secretion, blepharospasm and, in addition, due to chronic irritation in the cornea, there are signs of edema, vascularization, granulation, pigmentation and even ulcers, whether superficial or deep. The diagnosis is made by the veterinarian during the clinical examination through careful observation of the inversion of the eyelid margin towards the cornea and/or conjunctiva, and the surgical procedure is the indicated treatment. The objective of this work is to describe the procedure for resection of the nasal skinfold to correct entropion in a Pug dog.